Identification of Microplastics Types and Abundance in Mussels (Glauconome virens) from Tanah Merah Coastal Waters Meranti Island, Riau - Alwi, Ahmad; Amin, Bintal; Mubarak, Mubarak (Journal of Coastal and Ocean Sciences, 2025)
This study aims to analyze the types and abundance of microplastics in mussels (Glauconome virens) and differences in the abundance of microplastics between research stations in the coastal waters of Tanah Merah Village, Meranti Islands. Samples were taken from three different locations: residential areas, fishing ports, and mangrove areas. The number of mussel samples from the three stations was 54 individuals, with three size groups. Water quality parameters such as temperature, salinity, pH, and current speed were measured to determine the condition of the aquatic environment. Microplastics were analyzed using a microscope after going through a process of dissolving the mussel meat with a 10% KOH solution. The results showed that three types of microplastics were found, namely fiber, fragments, and films, with an average value of 46.50 particles/ind. Fiber type was the highest type found, followed by fragments and films. The highest abundance of microplastics was found in the mangrove area with an average value of 54.11 particles/ind, while the lowest was in the fishing port with 37.61 particles/ind. The abundance of microplastics in mussels showed significant differences (p<0.05) within the station. Possible causes of the difference were discussed